2019
DOI: 10.1021/acsomega.9b01481
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Iodine-Catalyzed Selective C-3 Benzylation of Indoles with Benzylic Alcohols: A Greener Approach toward Benzylated Indoles

Abstract: Iodine-catalyzed selective C-3 benzylation of indoles with benzylic alcohols is developed. The reaction proceeds with molecular iodine as the catalyst under ligand-, metal-, and base-free conditions and tolerates wide functionalities. The experimental observations account for the halogen-bond activation mechanistic pathway for the molecular iodine catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Many related transformations, including the use of Brønsted and Lewis acids, metal ions, or other supporters in a substoichiometric amount, have been reported by several reviews [3][4][5][6][7][8][9][10][11][12][13] and recent related advanced reports [14][15][16][17][18]. However, the requirement of toxic or expensive reagents, environmentally undesirable solvents, a high concentration of the mediator, prolonged reaction time, or high temperature make such a method less attractive from the green chemical aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Many related transformations, including the use of Brønsted and Lewis acids, metal ions, or other supporters in a substoichiometric amount, have been reported by several reviews [3][4][5][6][7][8][9][10][11][12][13] and recent related advanced reports [14][15][16][17][18]. However, the requirement of toxic or expensive reagents, environmentally undesirable solvents, a high concentration of the mediator, prolonged reaction time, or high temperature make such a method less attractive from the green chemical aspect.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous literature, these imidazole molecules were synthesized using transition-metal-catalyzed approaches, with transition metals such as copper, palladium, silver, etc., but these synthetic approaches practically have several drawbacks, such as moisture and air sensitivity, requirement of careful handling, hazardous and harsh conditions, heavy metal poisoning, and scale-up difficulties. These synthetic limitations have alerted chemists to find new environment-friendly pathways to construct small organic molecules. In view of the above considerations, metal-free organic reactions have gained much importance and have undergone alterations in both industry and academia.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above considerations, metal-free organic reactions have gained much importance and have undergone alterations in both industry and academia. Studies revealed that molecular iodine has the ability to functionalize C–H bonds to form new C–C and also C–heteroatom bonds. Iodine has also gained much attention in synthetic organic methodologies due to its low toxicity, metal-like characteristics, environmentally benign nature, and ease of handling in the laboratory, making it more suitable as a catalyst. , Accordingly, iodine serves as an alternative catalyst instead of transition metals in many organic reactions. , …”
Section: Introductionmentioning
confidence: 99%
“…Iodine has been applied widely as an effective catalyst for the functionalization of cyclic compounds. It shows good catalytic activity in the sulfenylation of indoles 21 and pyrazolones, 22 selenylation of 2H-indazole, 23 C-3 benzylation 24 and consecutive diazenylation/amination 25 of indoles, diazenylation of N-heterocyclic compounds, 26 C-N bond-forming of heterocyclic thiols and thiones, 27 arylation of substituted 1,4-naphthoquinones, 28 and rearrangement of 3-aminoindazoles. 29 Iodine-catalyzed systems have also been a good choice for oxidative transformations.…”
mentioning
confidence: 99%